Characterizing 90 accessions of sweetpotato in high rainfall sites of southern Nigeria - Egeonu, I.; Akoroda, M.O.; Tarawali, G. (2006)
A field collection of 90 sweetpotato (lpomoea batatas) accession collected. from various sources within and outside Nigeria were characterized at the llTA High Rainfall Station in Onne, Rivers State between June and August 2006. The objective of the study was to identify their distinctive characteristics and mountain of germplasm collection for evaluation and further research. Some of the accessions were found to be similar, based on whole-plant characteristics and were divided into 8 groups named after the first succession in which such characteristics were observed. The considerable variation observed in terms o/'leaf shape, leaf size, plant type und ground cover confirmed the large genetic varialibity, present in sweetpotato. Fammers interviewed during the germplasm collection activities in Bayelsa and Rivers state indicate that ability to spread fast und suppress weeds was a major consideration when selecting a sweetpotato varieties for cultivation. This highlights the need to include fammers in the selection process which will culminate in the release of new varieties for commercial cultivation in the country.